Inefficient Signalase Cleavage Promotes Efficient Nucleocapsid Incorporation into Budding Flavivirus Membranes - Lobigs, Mario (American Society for Microbiology, 2004)
The mechanism for efficient nucleocapsid (NC) uptake into flavivirus particles which form by budding through the membranes of the endoplasmic reticulum (ER) was investigated by using Murray Valley encephalitis virus as a model. Budding of flavivirus membranes is driven by the viral transmembrane proteins prM and E independently of NC interaction. We show that control of signalase cleavage of the multimembrane-spanning flavivirus polyprotein by the catalytic function of the viral protease is critical for efficient virus morphogenesis. In wild-type virus, signalase cleavage of prM remains inefficient until cleavage of capsid at the cytosolic side of the signal sequence separating the two proteins has occurred. This obligatory sequence of cleavages was uncoupled in a mutant virus with the consequence of greatly reduced incorporation of NC into budding membranes and augmented release of NC-free virus-like particles. Efficient signalase cleavage of prM in the mutant virus resulted in partial inhibition of cleavage of capsid by the viral NS2B-3 protease. Our results support a model for flavivirus morphogenesis involving temporal and spatial coordination of NC assembly and envelopment by regulated cleavages of an ER membrane-spanning capsid-prM intermediate.